Role of the Combination of Cyclin-Dependent Kinase Inhibitors (CDKI) and Radiotherapy (RT) in the Treatment of Metastatic Breast Cancer (MBC): Advantages and Risks in Clinical Practice - Gagliano, Ambrogio; Prestifilippo, Angela; Cantale, Ornella; Ferini, Gianluca; Fisichella, Giacomo; Fontana, Paolo; Sciacca, Dorotea; Giuffrida, Dario (Frontiers in Oncology, 2021)
Targeting cell cycle has become the gold standard for metastatic breast cancer (MBC), being cyclin-dependent kinase inhibitors (CDKIs) cornerstones of treatment. To date, no definite evidence regarding safety and efficacy of the combination of CDKIs plus radiotherapy (RT) is currently available. Purpose of this review is to collect data in favour or against the feasibility of the association of CDKIs + RT, evaluating its efficacy and describing its potential adverse events. By 2 letters to the editor, 1 review, 5 retrospective analyses and 3 case reports reviewed, CDKI + RT allows an overall satisfying disease control, proving to be effective and causing a grade of toxicity mainly influenced by the site of irradiation, leaning to favourable outcomes for sites as liver, spine or brain and to poorer outcomes for thoracic lesions or sites close to viscera; controversial evidence is instead for bone treatment. Toxicity also varies from patient to patient: in this context, the acknowledgment of toxicity and comorbidities history becomes of crucial importance. More studies are awaited for further deepening.